2023
DOI: 10.3390/ijerph20053893
|View full text |Cite
|
Sign up to set email alerts
|

Does Digitization Promote Green Innovation? Evidence from China

Abstract: Green innovation is an important strategy in seeking sustainable competitive advantages. This paper investigates the impact of enterprise digitization on green innovation and its mechanisms. We find that enterprise digital transformation has a significant effect on the promotion of green innovation. This positive effect mainly stems from the advantage of resource reallocation generated by enterprise digitalization that can alleviate financing constraints and raise risk-taking levels. Furthermore, the level of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 74 publications
0
12
0
Order By: Relevance
“…(1) Python text analysis method [ 37 ]. Dig in this paper are based on the collaboration of three steps: digitized vocabulary construction, text analysis of listed companies’ annual reports, and digitization index measurement.The first step is digitization and word set construction.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…(1) Python text analysis method [ 37 ]. Dig in this paper are based on the collaboration of three steps: digitized vocabulary construction, text analysis of listed companies’ annual reports, and digitization index measurement.The first step is digitization and word set construction.…”
Section: Methodsmentioning
confidence: 99%
“…(2) In the robustness test, this paper measures Dig based on digitization-related intangible assets as a replacement variable [ 37 ]. First, this paper collects detailed data on the intangible assets of Chinese A-share-listed manufacturing companies.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Besides known management consulting firms dealing with the subject (Deloitte, 2019;EY, 2020;PwC, 2022), a decent number of researchers are assessing the digital sustainability phenomenon in different aspects. Wang et al (2023) found a positive relationship between enterprise digitalization and green innovation, while Li et al (2023) concluded that digital financial inclusion positively correlates to green innovations. Berger et al (2021).…”
Section: Green Digitalization -Digital Solutions For a Greener Worldmentioning
confidence: 99%